Fatores associados às alterações neurocognitivas em pessoas vivendo com HIV maiores de 50 anos - Nascimento, Julio Cesar Matias do (2022)
ntroduction: With the advent of Antiretroviral Therapy (ART) it was noted that in recent years there has been improvement in the quality and life expectancy of people living with HIV (PLHIV) with the slowing of infection progression. As a result of prolonged exposure to both the virus and drugs and their toxicity, the role of HIV in the development of chronic diseases, even on ART, is evident. The Central Nervous System (CNS) is one of the tissues impacted by this infection, as even individuals with undetectable peripheral viral load have exhibited neurodegeneration, causing inflammation in the nervous tissue and contributing to the emergence of HIVassociated neurocognitive changes (HAND). HAND, including its most severe form, are more prevalent in PLHIV aged 50 years or older. Objective: The aim of this study was to identify the factors associated with neurocognitive changes in PLHIV aged 50 years and older. Methodology: This is a cross-sectional study, in patients over 50 years of age in follow-up at the Serviço de Atenção Especializada (SAE) Francisco Beltrão, Paraná, between April and November 2021. Were used as research instruments: sociodemographic questionnaire, Lawton scale, mini nutritional assessment (MAN), international HIV-associated dementia scale (IHDS), geriatric depression scale with 15 questions (GDS), gait speed (MV), fragility syndrome assessment, sarcopenia assessment. Results: 68.57% (n = 48) of the patients active in the SAE, older than 50 years and residents of Francisco Beltrão, Paraná, participated in the study, being 60.41% women (n = 29), 58.3% single (n = 14) or divorced (n = 14), with a mean age of 59.6 years. The mean age at diagnosis was 50.3 years, and the mean education level was 7.5 years. Participants had a mean of 1.7 diseases, with a mean use of 2.4 medications per patient. The mean current LT CD4+ was 561.5 cl/mm3, and 18.75% of the patients (n = 9) were classified as AIDS cases according to the Brazilian criteria. Current CV averaged 29241 cp/ml, and 89.58% of the participants had undetectable CV (n = 43). A total of 75% showed neurocognitive impairment by IHDS (n = 36), with 88.89% (n = 32) classified as asymptomatic (ANI) and the other 11.11% (n = 4) in the mild/moderate form (MND) of HAND. Conclusion: HAND is highly frequent in PLHIV older than 50 years, even on ART and undetectable CV, with the asymptomatic form being the most present. There were positive correlations for schooling, MAN and viral load at diagnosis and cognitive performance, as well as negative correlations for the number of diseases, number of medications and blood glucose, however, in the final model only education, viral load at diagnosis, and blood glucose remained as associated factors, together explaining 46% of the variability in the IHDS. Despite the relevance of this theme, neurocognitive assessment is not a reality in the routine of most health services that attend PWLH. Early diagnosis of HAND is important for better patient prognosis.